Physical activity of children primary school aged in the context their BMI - Miklánková, Ludmila; Rechtik, Zdeněk; Klimešová, Iva; Górny, Miroslav (Journal of Education, Health and Sport, 2016)
In the process of creating a positive attitude towards physical activities is very important to focus primarily on youngest age groups. Examine their habits and behavior in their lifestyles and to explore possibilities of interventions that promote positive behavioral habits in terms of their health. For the future generations of adults, then we can expect an increase in the benefits of physical fitness of the population, in a more responsible approach to their own health and the preference of a healthy lifestyle. The aim of the research is to determine the relationship between BMI and physical activity levels in children of school age. The research group consisted of 81 children from primary schools in the Czech Republic, the average age of 10.23 ± 0.42 years. Information about physical activity (active energy expenditure, number of steps) were obtained by ActiGraph. The level of BMI were evaluated in accordance with the points of reference of the Czech Republic. We confirmed significant relationship between the level of physical aktivity in the leisture time after school lessons and BMI of children (p <0.04). In boys were found statistically significant differences in physical activity at school (p <0.05) between the monitored categories of BMI. It is necessary to study habits and behavior of children in their lifestyle and look for possibilities that supports positive behavioral of interventions habits of in context of their health.